The Relationship of Coping Strategies with Stress, Anxiety and Depression among Medical Students - ur Rahman, Saeed; Rizwan, Hufsa Chandni; Khan, Muhammad Ashar Waheed; Malik, Saad Bashir; Minhas, Iftikhar Ahmed (Journal of Pakistan Psychiatric Society, 2022)
BackgroundPrevious studies have shown that medical students face high levels of stress, anxiety as well as depressive symptoms. Various coping strategies are used, which may be adaptive or maladaptive. Few studies in Pakistan have studied the association between emotional distress and coping methods.ObjectivesThis study aimed to evaluate the relationship between coping strategies and stress, anxiety and depression.MethodsIn a cross-sectional study, 273 undergraduate MBBS students (years 1 to 5) were assessed for stress, anxiety and depression using DASS scale, while coping strategies were assessed using Brief-COPE scale. Data were analyzed using SPSS 21.ResultsElevated levels of stress, anxiety and depression were found among the students. Denial, substance abuse and self-blame were positively correlated with, and predicted stress and emotional disturbance, while positive reframing was correlated with, and predicted lower level of stress and emotional disturbance. Behavioural disengagement was associated with depression.ConclusionsOur findings confirm that stress and emotional disturbance are quite frequent among medical students, and that they adopt a variety of coping methods, some of which are beneficial, others not. Students need to be educated about which coping methods are healthy and which ones are not. They should be helped to adopt the healthy ones with facilities such as counseling services, provision of extra-curricular activities and opportunities for healthy socialization.